An Empirical Analysis of Factors Affecting Financial Well-Being among MSMEs in Yogyakarta - Regas Panji Pratomo (Widya Dharma Journal of Business - WIJoB, 2026)
MSMEs still face issues of business sustainability, financial vulnerability, and low levels of financial well-being among business owners. This study aims to identify factors influencing the financial well-being of MSMEs in the Special Region of Yogyakarta, including financial literacy, financial traits, and financial behavior. The sampling technique was purposive, with the criteria being active MSMEs that have been operating for at least two years. Data analysis was conducted using Structural Equation Modeling (SEM-PLS). The results indicate that financial behavior negatively influences financial well-being; financial literacy positively influences financial behavior and financial traits; and both financial literacy and financial traits negatively influence financial well-being.